METODE PENDIDIKAN AKHLAK DALAM KITAB ADAB AL-MUFRAD KARYA IMAM BUKHARI - Muhiddin, Ihsan; Syafri, Ulil Amri (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2016)
Moral education is an important pillar in the establishment of the Islamic society. This is shown by Rasulullah who has been successfull educating his companions. They was a part of the society of ignorance that people become the best and most noble of all time. The process is carried Rasulullah can’t be separated from its methodology in fostering and educating akhlaq and character of the companions. This study seeks to examine the educational method used Rasulullah in educating akhlaq of the companions who are in Kitab Adab al-Mufrad. This Kitab is written exclusively by Imam Bukhari to focus specifically on the traditions relating to akhlaq and character. In education, the method becomes one of the most important elements that must be considered by education practitioners. Selection of appropriate methods of education that can affect the success of the educational process itself.